Pengembangan Komik Edukasi: Komikadp untuk Mengurangi Kekerasan dalam Pacaran - Eka Heriyani; Nurul Nurrachman; Cici Yulia (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The purpose of this research is to develop Komikadp educational comics. This study uses the research, research and development (R&D) 4D model. The subject of this research was an expert test by the UNTIRTA Guidance and Counseling lecturer, Mr. Arga Satrio Prabowo M, Pd. Field testing by all Muhammadiyah Junior High Schools throughout DKI Jakarta. Collecting data using interviews and assessment sheets consisting of a checklist for quantitative data and a description for qualitative data. After going through the define, design, develop stages, the Komikadp educational comic prototype obtained an expert test assessment and a very feasible field test with expert test details with an average value of 88.70% and field tests with an average value of 81.79%. The comments obtained from the expert test are that the comic is already very good, it needs further development and the story continues so that this comic does not stop here. The comments obtained from the field test of the media used are in accordance with the character of teenagers, interesting, creative, simple stories but rich in meaning, and very related to today's youth, it's just that the cause and effect need to be added and how to overcome them by counseling the BK teacher. The final decision obtained from the results of the expert test and field test is acceptable, appropriate, and feasible so that it can be used as a basis for carrying out the next stage without improvement